Moving Forward to a World Beyond 0.2, 0.5, and 0.8 Effects Sizes: New Cutoffs for School-Based Anti-Bullying Interventions - Panjeh, Sareh (Journal of interpersonal violence, 2023)
Effect sizes of school-based intervention are commonly described as small to moderate when using Cohen’s conventional effect size cutoffs (small [0.2], medium [0.5], and large [0.8]). However, Jacob Cohen’s rule of thumb might vary across different areas of research, nature of the intervention, and population, because effect sizes are context-dependent. Moreover, when planning research studies, minimum detectable effect sizes are used to calculate the sample size. In the present study, we investigate whether conventional effect size cutoffs (small [0.2], medium [0.5], and large [0.8]) represent the reported distribution of effect sizes in school-based anti-bullying intervention. To determine small, medium, and large effect sizes, we calculated the effect size distribution (ESD) using 50th percentile effect size (medium effect) of the distributions of effect sizes provided by a recent meta-analysis on school-based anti-bullying intervention. Also, the 25th and 75th percentile effects, as they are equidistant from the average effect size, were used redefining small and large effects, respectively. Results showed that 0.07, 0.123, and 0.227 represent small, medium, and large effect sizes in anti-bullying interventions. Our results indicate that Cohen’s suggested effect size thresholds (0.2, 0.5, and 0.8) overestimate effect sizes when compared to the real-world context of school based anti-bullying interventions. We also propose sample sizes required to reliably detect small, medium, and large percentile effect sizes in anti-bullying interventions.